The principle of legality and the provision “the judge is subject to the law” in the context of the doctrine of the development of law contra legem - A. S. Ghambaryan (Правоприменение)
The research subject. This study focuses on the correlation between the doctrine of development of law contra legem and the principle of legality, with a specific emphasis on the position that “judge submits to the law”.The purpose of the research. The objective of this research is to examine the compatibility of the doctrine of development of law contra legem with the principle of legality and evaluate the applicability of the "fourteen-year-old child" formula in assessing legislative regulations.Methodology. This research utilizes a legal analysis and conceptual examination of the doctrine of development of law contra legem and the principle of legality. It also involves a comparative analysis of legal principles within the post-Soviet context.Main results of the research. The analysis reveals that strict adherence to the principle of legality may not always align with societal interests. The doctrine of development of law contra legem provides an exception to the principle, allowing judges to evaluate and challenge the illogicality or unfairness of legislative regulations. The "fourteen-year-old child" formula, with its low standards for determining such flaws, safeguards judicial independence and shields judges from potential political pressures.Scope of application. The findings of this research can be applied within the legal framework, particularly in post-Soviet jurisdictions, where the interplay between the principle of legality and the doctrine of development of law contra legem is of significant relevance.Conclusion. The strict fulfillment of the requirements of the law (legality) is not a goal, but a means of ensuring the certainty and stability of the rule of law, the harmonization of public life. Based on the doctrine of the development of law contra legem, the communication of the post-Soviet judge and legislator should be viewed from the perspective of a three-layered relationship of “subordination – cooperation – opposition”.